MODERN APPROACHES TO TECHNICAL REGULATION OF THE RAILWAY - Lisohurskyi, O. M. (Science and Transport Progress, 2007)
In article modern problems in the field of development of technical plans of work of road and its structural divisions are considered. The analysis of existing methods of planning and their lacks is resulted at the organization of transportations in modern conditions. The characteristic of hierarchical levels of management, proceeding from restructuring a railway transportation is given. The system of classification of the parameters is resulted, allowing to detail the information on work of the railway and to apply it in mathematical models. Modern requirements to methodology of technical normalization are presented and basic elements of developed System of support of decisionmaking of technical normalization of work of road (СПР ТНЭРД) are described.